MENINGKATKAN KEMAMPUAN BERBAHASA ANAK MELALUI STRATEGI PEMBELAJARAN BERMAIN PERAN DI TK PEMBINA 5 KOTA TERNATE - Radjiman Ismail (Musawa: Journal for Gender Studies, 2022)
This article is the result of research that aims to improve children's language skills through role-playing learning strategies. Research methods using action research. There were 20 children in class B of TK Pembina 5 Ternate City. Language skills have an important role in early childhood development and development. Children can express ideas, ideas, thoughts, and desires through spoken language. Based on the results of the study in each cycle there was an increase in language skills in early childhood using role-playing strategies. Based on the results of this study it is recommended that Early Childhood Education teachers be able to use role-playing strategies to improve language skills in children.